Public Procurement of Energy Efficiency Services : Lessons from International Experience - Singh, Jas; Limaye, Dilip R.; Henderson, Brian; Shi, Xiaoyu (Washington, DC: World Bank, 2013)
This book explores energy savings performance contracts (ESPCs) as a means of overcoming some of the more difficult hurdles in promoting energy efficiency in public facilities. ESPCs represent a very attractive solution to many of the problems that are unique to public agencies, since they involve outsourcing a full project cycle to a service provider. From the detailed audit through implementation and savings verification, ESPCs can relieve public agencies of bureaucratic hassles, while service providers can secure the off-budget project financing and be paid from the actual energy savings, thus internalizing project performance risks. ESPC bidding also allows public agencies to select from a range of technical solutions, maximizing the benefit to the agency. Global experience suggests that ESPCs have been more effective at realizing efficiency gains than many other policy measures and programs, since the service providers have a vested interest in ensuring that a project is actually implemented. Many of the country governments interviewed for the study also saw enormous potential in bundling, financing, and implementing energy efficiency projects on a larger scale in the public sector, a method that increases the rate of efficiency gains and creates further benefits through economies of scale.